Demographic characteristics of Bryobia rubrioculus (Acari: Tetranychidae) reared on sour cherry leaves at different constant temperatures - Mohammad Ali Soleimani; Mohammad Khanjani; Babak Zahiri; Saeid Javadi Khederi (Persian Journal of Acarology)
The life history of Bryobia rubrioculus Scheuten (Acari: Tetranychidae) on sour cherry leaves was studied based on the age-stage, two-sex life table at nine constant temperatures (15, 17.5, 20, 22.5, 25, 27.5, 30, 32.5 and 33.5 ºC), 60 ± 5% RH and a photoperiod of 16: 8 (L: D) h. The longest and shortest total development time of the mites were obtained as 62.6 ± 1.66 and 14.2 ± 0.20 days at 15 and 32.5 ºC, respectively. As temperature increased from 15 to 32.5 ºC, the life span of the mites decreased from 83.5 ± 2.14 to 24.7 ± 0.39 days, respectively. The highest and lowest total fecundity was observed as 37.3 ± 1.63 and 6.3 ± 1.06 eggs at 17.5 and 15 ºC, respectively. The highest intrinsic rate of increase (r) was obtained as 0.1108 ± 0.005d-1 at 30 ºC. The mean generation time (T) ranged from 78.1 ± 2.8 to 19.1 ± 0.2 days at 15 and 32.5 ºC. Survi-vorship data (lx) of adult females were summarized and compared using the shape and scale parameters of the Weibull frequency distribution model. The lower temperature threshold (t) and thermal constant (k) of the immature stages were estimated using the Ikemoto and Takai linear model to be 8.9 ºC and 361.3 degree days (DD), respectively. The optimum temperatures were calculated by selected nonlinear models including Analytis1/Allahyari, Hilbert and Logan, and Logan-6 models to be 33.10, 33.90 and 32.40 ºC, respectively.